Bogie Running-in Test of Fault Monitoring Experiment on Rolling Stock Based on Microphone Array - Bo MA; Gongye YU; Ge YAN (机车电传动)
In view of the low degree of information and intelligence in running-in test of rolling stock bogies, it was difficult to realize fault diagnosis and fault location of bearings and gearboxes quickly and accurately in the test process. Microphone array technology was applied to running-in test, which could directly realize fault diagnosis and fault location through sound signals. Fault simulation experiments were carried out for the common faults of bogie bearing inner and outer rings. Acoustic signals generated by the faulty bearing were collected and analyzed. Signal envelope spectrum was obtained through specific data processing methods to realize fault diagnosis. At the same time, fault location was realized by combining the location algorithm based on arrival delay. In order to meet the needs of the field, a set of array brackets was designed to facilitate the accurate layout and flexible transformation of microphone arrays. The reliability and accuracy of the algorithm and array brackets were verified by simulation experiments.